Talent Management and Employee Retention: An Empirical Study in The Sudanese Telecommunication Sector - Alaa A. ABDALLA; Yousif A. ABDALLA (Communications of International Proceedings, 2023)
This study examines the effects of talent management practices, such as employee empowerment, appraisal and feedback, employee compensation, training, and career development, on staff retention in the Sudanese telecom industry. The conceptual framework of this study is based on employee perceptions and opinions on TM practices as they relate to employee retention. Employees in the telecom sector responded to surveys that were used to collect quantitative data. Two hundred seventy-eight individuals participated in the study. The results of the current study demonstrated a strong positive relationship between talent management practices (empowerment, compensation, employee appraisal, and training) and employee retention. Talent management practices in emerging economies such as Sudan have not received the attention they deserve in academic literature. Therefore, this paper addresses concerns over the lack of academic research on talent management and the speculation that it is the newest management fad. This paper aims to give a road map for firms to identify the essential talent management practices that influence employee retention.
Keywords: Talent Management Practices; Retention; Sudan.